Circularly polarized antennas and phased arrays for 5G applications - Hu, Yiyun (Nanyang Technological University, 2024)
The characteristics of millimeter waves, possessing abundant and clean spectrum resources, precisely meet the demand for high-speed wireless communication systems for operating bandwidth. Furthermore, to enhance the system’s capability in capturing signals and suppressing multipath interference, the millimeter-wave circularly polarized scanning antenna array is undoubtedly a good choice. Therefore, this dissertation focuses on the research of millimeter-wave circularly polarized antennas and their beam scanning arrays. The research focuses on the following aspects: (1) A patch antenna operating at a frequency of 28 GHz is designed to generate circularly polarized radiation. This is achieved by introducing asymmetry through circular notches on the ground plane, employing the concept of simple merger separation. This novel method can provide greater flexibility to achieve both impedance matching and circularly polarized matching over wider bands. A 1×8 beam scanning array is designed and fed by a special unaligned differential method, which improves the isolation of neighboring ports and makes the radiation direction map more symmetric. The gain of the antenna unit is 7.68 dBi, and the lowest axial ratio is 0.75 dB. The 1×8 beam scanning array can achieve ±50° wide angle scanning on the E-plane. The maximum gain of the array is 15.2 dBi, meanwhile the gain drop is not more than 2 dB over the scanning range. Importantly, the circularly polarized radiation can be achieved at all scanning angles. (2) To solve the drawback of the narrow bandwidth of the above antenna unit, a broadband circularly polarized planar magneto-electric dipole antenna is designed. This unit is improved based on the off-center fed folded long dipole by introducing the half-ring structure, which could make the unit more suitable for beam scanning arrays. Simultaneously, the aperture coupling feed is used to significantly broaden the radiation bandwidth. A 2×2 sub-array is designed using a T-shaped power divider to further enhance the antenna gain. The 4×4 beam scanning array adopts a similar feeding network as the 2×2 sub-array and the 1×4 antenna group placed along the phi=90° axis is used as the unit for beam scanning. The antenna unit has a S11 impedance matching bandwidth of 30.66-47.00 GHz(42.08%) and a 3 dB axial-ratio bandwidth of 28.62-37.6GHz (27.19%), with a maximum gain of 5.72 dBi. The S11bandwidth of the 2×2 sub-array is 29.2-49.3 GHz(51.21%), and the axial-ratio bandwidth is 33.25-37.36 GHz (11.64%), with a maximum gain of 11.2 dBi. Finally, the 4×4 scanning array could achieve a scanning angle of ±40° in the E-plane, with an S11 impedance matching bandwidth of 30.67-48.78 GHz. The scanning array has a maximum gain of 15.6 dBi, with a gain drop of no more than 2.5 dB over the scanning range. Circularly polarized radiation characteristics could be realized at all target directions.